Writing Instructions at a University and Identity Issues: A Systemic Functional Linguistics Perspective - Kanwal, Nagina; Amin Qadir, Samina; Shaukat, Kamran (International Journal of Emerging Technologies in Learning (iJET), 2021)
In this paper, we explore the discoursal identity in the academic writing of a postgraduate student from the University of Pakistan where English is the medium of instruction as well as taught as a foreign language. The study aims to find out the extent and the specific ways dominant conventions and practices enable and constrain meaning-making. It also helps to identify the role of social and institutional goals in shaping the discoursal identity of students. To achieve our objectives, we have conducted a linguistic analysis of the student’s academic texts by using Systemic Functional Linguistics. The findings from the linguistic analysis of academic texts are quite significant because the lexico-grammatical and discoursal choices in the academic texts reflect their writer’s desired disposition and their orientation within academia and their socio-cultural setting. Thus they reveal the writer’s discoursal identity and his positioning and affiliation with the academic community. The findings of the study provide significant implications for the reconceptualization of writing instructions at universities, also they point to the need to employ emerging technologies in the writing instructions program while not ignoring the students’ identity issues.